Pengaruh Idealisme, Tingkat Pengetahuan dan Love of Money Pada Persepsi Etis Mahasiswa Akuntansi - Eka Prilly Kartika Putri, Ni Luh; Krisna Dewi, Luh Gede (E-Jurnal Akuntansi; Vol 29 No 1 (2019), 2019)
This study aims to determine how students 'perceptions of accountants' unethical behavior with several variables, namely idealism, level of knowledge and love of money. This study uses questionnaire data as an instrument distributed to respondents. Respondents of this study were students of the accounting department of the Faculty of Economics and Business, Udayana University class 2015. The number of samples use 142 samples with nonprobability sampling technique. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis, the higher idealism in holding ethical principles, the students will always behave ethically, the higher level of knowledge possessed by students, the more ethical or responsive input will be and the higher love of money, the effort to do everything so that needs are met not in accordance with ethics. Keywords : Idealism; Level Of Knowledge; Love Of Money and Ethical Perception.